The British origins and the transformation of work culture in Australian industry - Oliver, Bobbie (RMIT Publishing, 2004)
The paper discusses the historical notion that the structure of skilled industrial trades in Australia is an example of 'British' diaspora, and then examines the impact and significance of local differences, especially as demonstrated in one site the Government Railway Workshops at Midland, Western Australia. The paper contends that extensive technological changes, such as occurred at Midland from the 1950s 70s, were accompanied by social changes in the workplace. It investigates the notion that the culture of the dominant skilled tradesmen underwent a radical shift during the period of investigation, with specific impacts upon themselves and the overall culture of the Workshops.